Symbols, Offerings, and Metallic Goods from the Puna and Quebrada de Humahuaca, Northwestern Argentina - (:unkn) unknown (Cotsen Institute of Archaeology Press, 2018)
This chapter addresses precious objects from the Puna and Quebrada de Humahuaca of northwestern Argentina, examining collections of metallic objects to determine their technological and iconographic characteristics, as well as associations with other goods. At the same time, comparisons are made with similar materials from Chile and Bolivia to propose interpretations of their symbolic, religious, and political implications.

Tarragó, M. N. (2018). Symbols, Offerings, and Metallic Goods from the Puna and Quebrada de Humahuaca Northwestern Argentina. En W. H. Isbell, M. I. Uribe, A. Tiballi, E. P. Zegarra (Eds.), Images in Action: The Southern Andean Iconographic Series, pp. 387-408. Los Ángeles: Cotsen Institute of Archaeology Press.
Fil: Tarragó, Myriam Noemí. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Keywords: Puna; Quebrada de Humahuaca; Northwestern Argentina; Metallic objects; Symbols; Offerings